Recovering from Hallucinations: A Qualitative Study of Coping with Voices Hearing of People with Schizophrenia in Hong Kong. (11th December 2012) - Ng, Petrus; Chun, Ricky W. K.; Tsun, Angela
Abstract : Auditory hallucination is a positive symptom of schizophrenia and has significant impacts on the lives of individuals. People with auditory hallucination require considerable assistance from mental health professionals. Apart from medications, they may apply different lay methods to cope with their voice hearing. Results from qualitative interviews showed that people with schizophrenia in the Chinese sociocultural context of Hong Kong were coping with auditory hallucination in different ways, including (a) changing social contacts, (b) manipulating the voices, and (c) changing perception and meaning towards the voices. Implications for recovery from psychiatric illness of individuals with auditory hallucinations are discussed.